METAPHORICAL FEATURES OF ENGLISH PHRASAL VERBS - Abdullaeva , Nozima Abdusalim qizi (Innovative Development in Educational Activities, 2024)
Phrasal verbs are becoming enormously popular and their polysemous and dissimilar meanings continuously emerging from the verb particle combinations are among the main focus of linguists. Phrasal verbs which contain both literal and metaphorical meanings cause difficulties in using appropriate contexts mainly for ESL or EFL students who are not aware of their root meanings. In this thesis, metaphorical meanings of phrasal verbs are defined with simple and exemplified explanations.